THE EFFECT OF STEM-BASED PHYSICS LEARNING ON STUDENT CREATIVITY AND PROBLEM SOLVING - Erik Mulandas; Linda Sekar Utami; M. Isnaini (INERCYS: Institute of Educational, Research, and Community Service, 2026)
STEM (Science, Technology, Engineering, and Mathematics)-based learning constitutes a critical aspect of physics education as it enables the holistic integration of multiple disciplines to foster 21st-century competencies. However, the low levels of students’ creativity and problem-solving skills in physics learning remain fundamental issues that require immediate attention. This challenge underscores the need for further investigation into the effectiveness of STEM-based learning in enhancing students’ creativity and problem-solving abilities. This study aims to analyze the effect of STEM-based physics learning on the creativity and problem-solving skills of senior high school students. The research employed a quasi-experimental method with a pretest–posttest control group design. Data were collected using a creativity assessment rubric and problem-solving ability tests validated by two expert lecturers. The collected data were analyzed using the Independent t-test and N-Gain test. The findings reveal a significant difference between the experimental and control groups in terms of creativity (sig. = 0.001; t = 5.41) and problem-solving skills (sig. = 0.002; t = 4.87). The N-Gain scores in the experimental group reached 0.54 for creativity and 0.49 for problem-solving skills, both categorized as moderate, whereas the control group only achieved low categories. These results indicate that STEM-based learning is effective in enhancing students’ competencies. This study provides a significant contribution to the advancement of physics education at both national and international levels through the reinforcement of innovative STEM-based instructional models. Furthermore, the findings are expected to serve as a reference for future research, particularly in the development of instructional strategies aimed at improving creativity and problem-solving skills, as well as to encourage more in-depth and applicable follow-up studies.